Workshop Penerapan Strategi Pemasaran Dalam Meningkatkan Penjualan Produk Kopi Sanrego - Tangngisalu, Jannati; Alam, Syamsu; Syafruddin, Muhammad; Bungatang, Bungatang; Aswad, Abul (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
The Sanrego Cooperative is a Sanrego coffee producer located in Bulukumba district, South Sulawesi. There are 2 types of products produced by the Sanrego cooperative, namely Sanrego coffee and Djago coffee. This Sanrego coffee product has a distinctive taste and is made from Sanrego wood mixed with ginger. The two types of basic ingredients are herbal ingredients that have been trusted for a long time as traditional medicines without side effects. While Sanrego wood itself has been studied by several finochemical experts at several universities in Eastern Indonesia, it contains alkolids, sitosterol, glycosides which function to inhibit the development of bacteria in the human body. In increasing its sales level, the Sanrego cooperative uses several methods such as direct consumer sales through outlets or stalls in a number of places, online sales and sales through Sanrego cafes which were established to accommodate coffee connoisseurs. The Sanrego Cooperative, which is traditionally prepared by professional hands, is targeted to become the number one coffee in Bulukumba, including South Sulawesi. This workshop and discussion resulted in several recommendations that could be made by the Sanrego Cooperative in improving its business performance in the future.